Effect of acetylation on the physico‐chemical properties of Indian Horse Chestnut (Aesculus indica L.) starch. Issue 3 (20th January 2015) - Shubeena,; Wani, Idrees Ahmed; Gani, Adil; Sharma, Paras; Wani, Touseef Ahmed; Masoodi, Farooq Ahmad; Hamdani, Afshan; Muzafar, Sabeera
Abstract : The present work was carried out to study the effect of acetylation (0, 3, 6, and 9 g vinyl acetate/gram starch) on the physico‐chemical properties of starch, isolated from Indian horse chestnut ( Aesculus indica ). Work on starch acetylation and characterization from Indian horse chestnut has not been reported so far in the literature. Moisture, protein, fat, and ash content of native starch was found as 5.97%, 0.27%, 0.22%, and 0.01%, respectively. Acetyl content, swelling index, solubility index, and water absorption capacity of acetylated starch increased with increase in acetyl %, whereas, pasting temperature, syneresis, and amylose content reduced with acetylation. Granule morphology under the scanning electron microscopy revealed that granules were round, oval, irregular, or elliptical with smooth surfaces.